2020
DOI: 10.1210/clinem/dgaa881
|View full text |Cite
|
Sign up to set email alerts
|

Primary Adrenal Insufficiency in Childhood: Data From a Large Nationwide Cohort

Abstract: Context Primary adrenal insufficiency (PAI) is a rare and potentially life-threatening condition, poorly characterized in children. Objective to describe causes, presentation, auxological outcome, frequency of adrenal crisis and mortality of a large cohort of children with PAI. Patients and methods data from 803 patients from 8 centers of Pediatric Endocrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
2
21
0
7
Order By: Relevance
“…FGD is a group of rare conditions characterized by a lack of response to ACTH and the presence of isolated glucocorticoid deficiency. FGD usually presents in the early period of life with hypoglycemia, convulsions, prolonged jaundice, and marked skin hyperpigmentation ( 6 , 11 , 14 ). Several defects in MC2R, MRAP, MCM4, NNT, and TXNRD2 genes are related to FGD or related conditions, and MC2R variants cause about 25% of all cases of FGD ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGD is a group of rare conditions characterized by a lack of response to ACTH and the presence of isolated glucocorticoid deficiency. FGD usually presents in the early period of life with hypoglycemia, convulsions, prolonged jaundice, and marked skin hyperpigmentation ( 6 , 11 , 14 ). Several defects in MC2R, MRAP, MCM4, NNT, and TXNRD2 genes are related to FGD or related conditions, and MC2R variants cause about 25% of all cases of FGD ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the pituitary-adrenal axis affects the synthesis of bile acids and that cortisol deficiency may have a role in inducing cholestasis (2)(3)(4)(5). Primary adrenal insufficiency (PAI) is a potentially life-threatening disease characterized by impaired secretion of glucocorticoids eventually associated with mineralocorticoid and adrenal androgen deficiency or excess (6,7). Although PAI is known to be a possible cause of NC, cholestasis has not been reported as its isolated clinical manifestation so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause of pediatric PAI is congenital adrenal hyperplasia (CAH) of 21-hydroxylase deficiency (21OHD). 1) During the past decade, a number of rare monogenic disorders with PAI have been reported. The diagnosis of AI in children and young infants is frequently delayed because it has nonspecific, vague clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired adrenal steroidogenesis, adrenal dysgenesis and adrenal destruction are the most common causes of primary adrenal insufficiency in children, with congenital adrenal hyperplasia (CAH) and autoimmune destruction being the most frequent [ 17 ]. Symptoms of adrenal insufficiency range from insidious to severe and include fatigue, weakness, weight loss, nausea, abdominal pain, vomiting, severe dehydration unresponsive to intravenous fluid, and coma [ 18 ]. Infants may also show poor feeding and impaired growth.…”
Section: Introductionmentioning
confidence: 99%